2015
DOI: 10.1093/eurheartj/ehv114
|View full text |Cite
|
Sign up to set email alerts
|

Haeme oxygenase signalling pathway: implications for cardiovascular disease

Abstract: Evidence now points to the haeme oxygenase (HO) pathway as a possible actor in modulating risk for cardiovascular disease (CVD). In particular, the HO pathway may represent a key endogenous modulator of oxidative, inflammatory, and cytotoxic stress while also exhibiting vasoregulatory properties. In this review, we summarize the accumulating experimental and emerging clinical data indicating how activity of the HO pathway and its products may play a role in mechanisms underlying the development of CVD. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 190 publications
(155 reference statements)
1
57
0
3
Order By: Relevance
“…8 Heme oxygenase-1 (HO-1) is an increasingly recognized modulator of cardiovascular risk and its expression is inducible by physiologic stressors such as circulating phospholipids, vascular injury, hypertension, hyperglycemia, smoking, and laminar shear stress. 8, 33-36 In autopsy samples of human coronary arteries, HO-1 activity was shown to be overexpressed in atherosclerotic plaques and to correlate with the degree of stenosis. 37 HO-1 has also been demonstrated to be an essential driver of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Heme oxygenase-1 (HO-1) is an increasingly recognized modulator of cardiovascular risk and its expression is inducible by physiologic stressors such as circulating phospholipids, vascular injury, hypertension, hyperglycemia, smoking, and laminar shear stress. 8, 33-36 In autopsy samples of human coronary arteries, HO-1 activity was shown to be overexpressed in atherosclerotic plaques and to correlate with the degree of stenosis. 37 HO-1 has also been demonstrated to be an essential driver of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…8 In animal models, physiologic concentrations of CO in vivo promote vascular and endothelial integrity, 9, 10 prevent hypoxia-induced apoptosis, 11 and attenuate the development of obesity. 12 By contrast, elevated endogenous CO concentrations have been found to antagonize NO-mediated vasodilation, 13 promote hyperglycemia, 14 foster oxidative stress, 15 and mediate the hypertensive response to physiologic stress in several disease models.…”
Section: Introductionmentioning
confidence: 99%
“…; Durante ; Fredenburgh et al. ). HO‐1 has also been shown to be significantly reduced in PAD patients, and has been implicated as an independent predictor of PAD (Signorelli et al.…”
Section: Mechanismsmentioning
confidence: 99%
“…Bilirubin can protect against oxidation of lipids, and its antioxidant effect exceeds that of vitamin E toward lipid peroxidation (Stocker et al 1987;Sedlak and Snyder 2004). In addition to its protective role against oxidative stress, HO-1 also contributes to angiogenesis, and the HO-1 signaling pathway has been implicated in modulating the risk for cardiovascular diseases (Idriss et al 2008;Durante 2010;Fredenburgh et al 2015). HO-1 has also been shown to be significantly reduced in PAD patients, and has been implicated as an independent predictor of PAD (Signorelli et al 2016).…”
Section: Ros As Signaling Moleculesmentioning
confidence: 99%
“…We also find intriguing the possibility that iron depletion in menstruating women may be cardioprotective. We had previously been aware of the potential role of iron as a by-product of haeme oxygenase activity in mediating cardiometabolic risk,2 with a number of community studies having reported equivocal findings when examining the relation between either iron or ferritin with respect to outcomes 3–6. It is our impression that heterogeneity in prior study results may be related to differences in participant sampling methods, the iron measures used (ferritin, total iron-binding capacity, transferrin saturation, serum iron and dietary iron intake) and presence of potential confounding variables that could influence both iron levels and a given outcome of interest (eg, inflammation and genetic variants).…”
mentioning
confidence: 99%